2017
DOI: 10.5812/ijp.10095
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Clinical and Imaging Findings in Children with Diagnosis of Acute Appendicitis

Abstract: Objectives: This study is an evaluation of the accuracy of ultrasonography (USG), computed tomography (CT), and Alvarado score (AS) in the diagnosis and management of acute appendicitis in children. Methods: Records of pediatric patients admitted to the pediatric emergency department (ED) between 2008 and 2012 were evaluated retrospectively. Patient data from the national electronic health information system was screened and those with complete clinical and imaging findings (AS, preoperative USG and/or CT imag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…In addition, ultrasound diagnostics is far more accessible. In a recently published study by a group of Turkish authors, CT showed greater sensitivity and specificity in relation to ultrasound, although it did not lead to a reduction in the number of negative appendectomies in children [20]. However, optimizing ultrasound diagnostic quality resulted in 67% decreased utilizing of CT imaging in patients with suspected acute appendicitis, and consequently in significant decreases in hospital costs [21].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, ultrasound diagnostics is far more accessible. In a recently published study by a group of Turkish authors, CT showed greater sensitivity and specificity in relation to ultrasound, although it did not lead to a reduction in the number of negative appendectomies in children [20]. However, optimizing ultrasound diagnostic quality resulted in 67% decreased utilizing of CT imaging in patients with suspected acute appendicitis, and consequently in significant decreases in hospital costs [21].…”
Section: Discussionmentioning
confidence: 99%